Atomic-scale observation of solvent reorganization influencing photoinduced structural dynamics in a copper complex photosensitizer. Issue 10 (14th February 2023) - Katayama, Tetsuo; Choi, Tae-Kyu; Khakhulin, Dmitry; Dohn, Asmus O.; Milne, Christopher J.; Vankó, György; Németh, Zoltán; Lima, Frederico A.; Szlachetko, Jakub; Sato, Tokushi; Nozawa, Shunsuke; Adachi, Shin-ichi; et al.
Abstract : Ultrafast X-ray measurements reveal the mechanisms of the solvent influence on photosensitizing activity. Abstract : Photochemical reactions in solution are governed by a complex interplay between transient intramolecular electronic and nuclear structural changes and accompanying solvent rearrangements. State-of-the-art time-resolved X-ray solution scattering has emerged in the last decade as a powerful technique to observe solute and solvent motions in real time. However, disentangling solute and solvent dynamics and how they mutually influence each other remains challenging. Here, we simultaneously measure femtosecond X-ray emission and scattering to track both the intramolecular and solvation structural dynamics following photoexcitation of a solvated copper photosensitizer. Quantitative analysis assisted by molecular dynamics simulations reveals a two-step ligand flattening strongly coupled to the solvent reorganization, which conventional optical methods could not discern. First, a ballistic flattening triggers coherent motions of surrounding acetonitrile molecules. In turn, the approach of acetonitrile molecules to the copper atom mediates the decay of intramolecular coherent vibrations and induces a further ligand flattening. These direct structural insights reveal that photoinduced solute and solvent motions can be intimately intertwined, explaining how the key initial steps of light harvesting are affected by the solvent on the atomic time and length scale. Ultimately, this work takes a step forward in understanding the microscopic mechanisms of the bidirectional influence between transient solvent reorganization and photoinduced solute structural dynamics.